3D chiral mechanical metamaterial for tailored band gap and manipulation of vibration isolation. (15th November 2022) - Zhao, Pengcheng; Zhang, Kai; Qi, Liyuan; Deng, Zichen
Abstract: This paper studies the dynamic properties of a 3D chiral mechanical metamaterial, which largely depend on tacticity describing the connection forms of the chiral unit. Based on the finite element theory and Bloch's theorem, a dynamic model of the 3D chiral mechanical metamaterial is established to analyze the band structures and transmission responses. The isotactic configuration converts longitudinal waves into transverse waves due to the chirality, which results in the vibration attenuation of the longitudinal wave that is independent on band gaps. The band gaps appear at the band structures of the syndiotactic configuration, and the generation mechanism is related to the vibration mode of ligaments, which can be used to predict band gap. The samples were manufactured by additive manufacturing to vibration transmission test for verifying the dynamic responses and the band gaps of the 3D chiral mechanical metamaterial with different tacticities. In addition, the gradient design and programmable design are used to further expand the vibration attenuation region, which has the potential for practical applications of vibration suppression.